Electrocardiogram analysis of hyperlipidemia-induced wistar rats using wireless mice electrocardiogram - Maulana, Harfi; Ridwan, Ahmad; Suprijanto; Kusumawardani, Shanty Rahayu; Fitri, Lulu Lusianti (Penerbit Universiti Kebangsaan Malaysia, 2023)
Coronary heart disease (CHD) is a life-threatening disease caused by obstruction of the coronary arteries that interferes with blood flow known as atherosclerosis. Hyperlipidemia, a risk factor of atherosclerosis, is characterized by excessive concentrations of total cholesterol, LDL, and triglycerides with low concentrations of HDL. A high-fat diet (HFD) contributes to the progression of atherosclerosis, CHD, and other cardiovascular diseases. This study aims to measure electrocardiography (ECG) waves of hyperlipidemia-induced rats. Twenty rats were fed different diets for eight weeks, i.e., the control group (normal diet) and the HFD group (high-fat diet). Their ECG was recorded using a Wireless Mice Electrocardiogram (WIM ECG) for 5-10 min. After eight weeks, the HFD group showed a significantly higher lipid profile concentration (cholesterol: 179.03 mg/dL, triglyceride: 149.11 mg/dL, LDL: 123 mg/dL, HDL: 29.15 mg/dL) than the control. This hyperlipidemic condition causes a significant change in some characteristics of the ECG wave. At week 8, the characteristic ECG wave duration for the HFD groups was RR intervals (176.5 ms), QT intervals (123.5 ms), T waves (33.6 ms), P wave (27.4 ms), QRS interval (64.9 ms), ST-segment (23.7 ms), and heart rate (334 bpm). This study concludes that long-period HFD feeding in rats leads to hyperlipidemia and causes changes in the characteristics of ECG waves.